The Ruling on Conducting Manual Examination on Patients in Islamic Jurisprudence-A Jurisprudential Study Based on the Purposes of Islamic Law - Al-Share, Safia Ali; Al Omari, Randa Abdelkarim Abdelhafiz (Journal of Posthumanism, 2025)
This study aims to disprove the Islamic ruling on conducting manual medical examinations on patients by examining the texts and principles of Islamic law. The significance of this research lies in its response to the concerns of medical students, who often experience ethical dilemmas during the early stages of their medical practice.The researcher adopts an analytical approach to Islamic legal texts to derive a ruling on this issue. The study concludes that conducting manual examinations on patients is permissible when dictated by necessity or genuine need. This study provides an analytical examination of the Islamic ruling on conducting manual medical examinations on patients, particularly in cases where there is a gender difference between the physician and the patient. Further study should be conducted on the issue of medical treatment in Islamic law, linking it with contemporary medical practices.